2016
DOI: 10.4049/jimmunol.1501202
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Dendritic Cells Promote Th Polarization, whereas Conventional Dendritic Cells Promote Th Proliferation

Abstract: Monocyte-derived dendritic cells (moDCs) dramatically increase in numbers upon infection and inflammation; accordingly, we found that this also occurs during allogeneic responses. Despite their prominence, how emergent moDCs and resident conventional DCs (cDCs) divide their labor as APCs remain undefined. Hence, we compared both direct and indirect presentation by murine moDCs versus cDCs. We found that, despite having equivalent MHC class II expression and in vitro survival, moDCs were 20-fold less efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 65 publications
6
65
0
1
Order By: Relevance
“…Whether such cells are poor APCs remains undetermined. Indeed, we had previously shown that moDCs were capable of inhibiting T cell proliferation induced by cDCs (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether such cells are poor APCs remains undetermined. Indeed, we had previously shown that moDCs were capable of inhibiting T cell proliferation induced by cDCs (23).…”
Section: Discussionmentioning
confidence: 99%
“…They have been observed to arise in many different types of infections, including Listeria monocytogenes (26), Leishmania major (39), and Trypanasoma (40), as well as participating in the pathogenesis of a number of inflammatory conditions, such as asthma (41) and experimental autoimmune encephalomyelitis (37). They can also be induced by systemic inflammatory meditators, for example TLR signaling through LPS administration (42), or in systemic GM-CSF transgenesis (23). Nevertheless, despite an increasingly broad understanding of their biology and function, the role of moDCs in the setting of organ transplantation has been less well characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main mechanisms have been proposed. First, monocytes may directly kill either the effector T cells or antigen-bearing cDCs via NO 79,121,122 . Second, killing may result from the sequestration of cysteine, a process that can be counterbalanced by cysteine supplementation 123 .…”
Section: Box 2 | Classical Dendritic Cell Subsets In Cross-presentationmentioning
confidence: 99%
“…Many reports indicate, however, that monocytederived DCs stimulate T cells poorly despite their prodigious capacity to uptake and process Ags (18,28). Flow cytometric analysis of freshly isolated tumor DCs from Zbtb46-DTR and WT bone marrow chimeras revealed that they express similar levels of intracellular iNOS and TNF.…”
Section: Tumor Dc3 Stimulate Ctl Proliferationmentioning
confidence: 99%